Guest Editorial Vol5 no2 - Deirdre Watson (Scottish Journal of Residential Child Care)
Some young people have a positive care journey with reasonable outcomes as evidenced in Extraordinary Lives: creating a positive future for looked-after children and young people in Scotland (Social Work Inspection Agency, 2006). Achieving consistency of care, however, has remained elusive as outlined in reports such as Let's Face It (Paterson, Watson, and Whiteford, 2003). During the eighteen years I spent as Director of Who Cares? Scotland, I witnessed many new initiatives but was often somewhat frustrated at the unrealistic way in which some of these were resourced. The introduction of initiatives may lead us to believe that the care offered to looked-after children is improving. Initiatives, however, require to be adequately resourced in terms of finance and the promotion of cultures which support aspirational plans. Sadly, there is still a stigma and a culture of low expectation associated with residential care. If the best possible service is to be provided for looked-after children and young people, policymakers must be realistic about the effort that will take and the investment that still has to be made. To help us get to that point perhaps we need a 'hearts and minds' campaign to change thinking and to combat some of the current negative attitudes that surround young people.